2014
DOI: 10.3168/jds.2012-6184
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Aflatoxin M1 in dairy products sold in Şanlıurfa, Turkey

Abstract: The aim of this study was to detect the presence of aflatoxin M₁ (AFM1) in samples of raw milk (n=38), UHT milk (n=12), white pickled cheese (n=50), and yogurt (n=50) collected from the Şanlıurfa city markets and locally produced dairy products by ELISA. The mean contamination rates were 56.74 ± 40.32, 43.1 ± 23.19, 103.2 ± 29.13, and 55.28 ± 12.68 ng/kg, respectively, for raw milk, UHT milk, white pickled cheese, and yogurt. According to the data, 21 (55%) raw milk, 3 (25%) UHT milk, 10 (20%) white pickled ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…According to Elsayed and Abdelfatah [19] and Temamogullari and Kanici [20], AFM1 was detected in both yoghurt and processed cheese samples in lower percentage, while Iqbal and Asi [21] detected the toxin in both products with higher percentage than our results. Regarding Domiati cheese, 46.7% of the samples were contaminated with AFM1 with levels ranged between 22.60 -74.23 ng/kg and a mean value of 47.68 ± 6.94.…”
Section: Resultscontrasting
confidence: 66%
“…According to Elsayed and Abdelfatah [19] and Temamogullari and Kanici [20], AFM1 was detected in both yoghurt and processed cheese samples in lower percentage, while Iqbal and Asi [21] detected the toxin in both products with higher percentage than our results. Regarding Domiati cheese, 46.7% of the samples were contaminated with AFM1 with levels ranged between 22.60 -74.23 ng/kg and a mean value of 47.68 ± 6.94.…”
Section: Resultscontrasting
confidence: 66%
“…In the study by Berhanu et al (under preparation), spiked samples have been used as reference material, with recovery above 70%, but this is lower compared to the study by Ismail et al ( 2017 ) where recovery was between 94 and 100%, using the same kit. The same ELISA has been used by several other studies including to test fermented milk samples (Temamogullari and Kanici 2014 ; Farah Nadira et al 2017 ). Yoghurt was not spiked in this study, but other studies have found the recovery rates of spiked yoghurt samples being lower than milk samples (Kim et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between aflatoxin concentrations in food and acute illness (i.e., aflatoxicosis) has been established and has led to regulatory limits in many countries, but little is known about specific threshold levels associated with other adverse health effects (Strosnider et al, 2006). While a number of studies in certain countries (e.g., Brazil, China, Sudan, and Turkey) have reported aflatoxin levels in dairy products exceeding recommended or regulatory limits (Bahrami et al, 2015;Bilandžić et al, 2014;Elzupir & Elhussein, 2010;Iha et al, 2011;Raul et al, 2012;Temamogullari & Kanici, 2014;Xiong et al, 2018), the risk to human health is not clear. It has been estimated that aflatoxin exposure in nuts and maize may play a causative role in anywhere from 4.6-28.2% of global hepatocellular carcinoma, or liver cancer, cases (Liu & Wu, 2010).…”
Section: Chemical Contaminantsmentioning
confidence: 99%